Chiral bicyclic NHC/Ir complexes for catalytic asymmetric transfer hydrogenation of ketones. Issue 84 (7th September 2015) - Yoshida, Kazuhiro; Kamimura, Takumi; Kuwabara, Hiroshi; Yanagisawa, Akira
Abstract : A diverse series of chiral bicyclic NHC/Ir complexes were prepared via a previously developed divergent synthesis of chiral imidazolium salts. Abstract : A diverse series of chiral bicyclic NHC/Ir complexes were prepared via a previously developed divergent synthesis of chiral imidazolium salts. Among the complexes, 8dz was found to be an excellent catalyst precursor for the Ir-catalyzed asymmetric transfer hydrogenation of ketones. The reaction of ketones with8dz proceeded smoothly to give corresponding alcohols with high enantioselectivities (up to 98%) and productivities (TON up to 4500).